Precursor‐derived versus de‐novo carcinogenesis depends on lineage‐specific mucin phenotypes of intramucosal gland‐forming gastric neoplasms. Issue 5 (19th August 2013) - Nishimura, Rie; Mukaisho, Ken‐ichi; Yamamoto, Hiroto; Sonoda, Ayano; Andoh, Akira; Fujiyama, Yoshihide; Hattori, Takanori; Sugihara, Hiroyuki
<x xml:space="preserve">Abstract</x> Aims To clarify the lineage‐specific carcinogenesis of gland‐forming gastric neoplasms, by characterizing mucin phenotypes and proliferation patterns immunohistochemically using monoclonal antibodies against MUC2, MUC5AC, MUC6, CD10 and Ki67. Methods and results We analysed 49 gland‐forming intramucosal neoplasms, including 15 non‐invasive low‐grade neoplasms (group A), 10 non‐invasive high‐grade neoplasms (group B) and 24 intramucosal adenocarcinomas (group C). The mode of gland‐forming gastric carcinoma development was different between the intestinal and gastric lineages. The pure intestinal‐type accounted for 93% of group A, 50% of group B and 4.2% of group C tumours. A zonal pattern of cell proliferation was well retained in group A tumours and was lost size‐dependently in group B tumours. These findings suggest that non‐invasive low‐grade neoplasms of the intestinal lineage progress to non‐invasive high‐grade neoplasms, but rarely to intramucosal adenocarcinomas. In tumours of the gastric lineage, which exhibited pure gastric or mixed phenotypes, the polarity of cell proliferation and differentiation was well retained in small (≦5 mm) tumours but was lost in larger tumours in groups B and C. Conclusions Intramucosal adenocarcinomas of the gastric lineage may often arise de novo, develop in the proper gastric mucosa, and are partially derived from non‐invasive high‐grade neoplasms.